(untitled) (Agricultural Engineering, 2022)
Tractors are used for various types of field work, as well as for transport on public roads, in difficult and changing environmental conditions. The main goal of the study was to analyze the changes of trace elements in engine oil during various field works. For this purpose, engine oils from two tractors were selected for the study. These tractors were coupled with: a cultivator, a reversible plow, a tillage-sowing unit, and a trailer. The samples were taken at the beginning and after the field work with a given unit was completed. The instrumental chemical analysis method HDXRF was used to determine changes in the content of the trace elements: Cr, Cu, Fe, Pb, Ni, Ca, P, Zn, and Mo in the engine oil. The comparison of oil from tractors coupled with various agricultural machines allowed the conclusion that the distribution of the consumption of tested metals, as well as the concentrations of individual elements, differed significantly depending on the coupled machine. The research showed that agricultural treatments with a cultivator caused the highest percentage of wear-induced changes in the content of metal elements such as Cr, Cu, and Pb. On the other hand, the operation of a tractor coupled with a tillage-sowing unit resulted in the vehicle’s accelerated wear.